Using a k-means clustering to identify novel phenotypes of acute ischemic stroke and development of its Clinlabomics models - Jiang, Yao; Dang, Yingqiang; Wu, Qian; Yuan, Boyao; Gao, Lina; You, Chongge (Frontiers in Neurology, 2024)
Objective: Acute ischemic stroke (AIS) is a heterogeneous condition. To stratify the heterogeneity, identify novel phenotypes, and develop Clinlabomics models of phenotypes can conduct more personalized treatments for AIS.In a retrospective analysis, consecutive AIS and non-AIS inpatients were enrolled. An unsupervised k-means clustering algorithm was used to classify AIS patients into distinct novel phenotypes. Besides, the intergroup comparisons across the phenotypes were performed in clinical and laboratory data. Next, the least absolute shrinkage and selection operator (LASSO) algorithm was used to select essential variables. In addition, Clinlabomics predictive models of phenotypes were established by a support vector machines (SVM) classifier. We used the area under curve (AUC), accuracy, sensitivity, and specificity to evaluate the performance of models.Results: Of the three derived phenotypes in 909 AIS patients (median age 64 (IQR:17) years, 69% male), in phenotype 1 (N=401), patients were relatively young and obese and had significantly elevated levels of lipids. Phenotype 2 (N=463) was associated with abnormal ion levels. Phenotype 3 (N=45) was characterized by the highest level of inflammation, accompanied by mild multiple-organ dysfunction. The external validation cohort prospectively collected 507 AIS patients (median age 60 (IQR:18) years, 70% male). Phenotype characteristics were similar in the validation cohort. After LASSO analysis, Clinlabomics models of phenotype 1 and 2 were constructed by the SVM algorithm, yielding high AUC (0.977, 95%CI: 0.961 -0.993 and 0.984, 95%CI: 0.971 -0.997), accuracy (0.936, 95%CI: 0.922 -0.956 and 0.952, 95%CI: 0.938 -0.972), sensitivity (0.984, 95%CI: 0.968 -0.998 and 0.958, 95%CI: 0.939 -0.984), and specificity (0.892, 95%CI: 0.874 -0.926 and 0.945, 95%CI: 0.923 -0.969).In this study, three novel phenotypes that reflected the abnormal variables of AIS patients were identified, and the Clinlabomics models of phenotypes were established, which are conducive to individualized treatments.